Q: Factor x squared - 12x plus 27 equals 0?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

2(x - 2)(x - 4)

(3x - y+ 2)(3x + y + 2)

30+12x = 6(5+2x)

x2+12x+5 = 3 x2+12x+5-3 = 0 x2+12x+2 = 0

6(x + 1)(x + 1)

Related questions

2(x - 2)(x - 4)

(3x - y+ 2)(3x + y + 2)

30+12x = 6(5+2x)

x2+12x+5 = 3 x2+12x+5-3 = 0 x2+12x+2 = 0

2(x + 4)(x + 2)

6(x + 1)(x + 1)

(x - 8)(x - 4)

(2x - 3)(2x - 3)

(2x - 1)(6x + 5)

(-3, -5)

The answer is (2x^2+3)(4x+1)

4x(4x^2 + 3x + 1)